Analisis Pengaruh E-Service Quality terhadap Kepuasan Pengguna Aplikasi Dompet Digital DANA di Wilayah Jakarta Barat - Reza Mahendra; Qori Halimatul Hidayah (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
This research aims to analyze the quality of electronic services (E-Service Quality) on user satisfaction of the DANA digital wallet application in the West Jakarta area. The evolution of financial technology (fintech) in Indonesia has encouraged rapid growth in the use of digital wallets, including DANA which is recorded to have more than 200 million users by 2024. However, this rapid growth is still marred by a number of user complaints regarding system reliability, service response speed and transaction security. Therefore, this study is important to evaluate how much e-service quality dimensions influence user satisfaction levels. The research method used is a quantitative approach with an associative type of research. Data was collected through questionnaires from 100 respondents who were active users of the DANA application in the West Jakarta area using a purposive sampling technique. Data analysis was carried out using SPSS software through validity tests, reliability tests, and simple linear regression analysis. The research results show that E-Service Quality has a positive and significant effect on user satisfaction of the DANA application with a coefficient of determination (R Square) of 0.907, which means that 90.7% of the variation in user satisfaction can be explained by the E-Service Quality variable, while the remaining 9.3% is influenced by other factors outside the research model. The results of the significance test (t test) show a significance value (Sig. < 0.05) which indicates that the influence of E-Service Quality on user satisfaction has been proven to be statistically significant. The results of this study are expected to serve as evaluation material for DANA application managers in improving the quality of digital services, particularly in terms of efficiency, system reliability, security, and user responsiveness. Furthermore, this research is expected to provide theoretical contributions to the development of studies in the field of information systems and digital service management.